Health and spirituality from the cultural identities, in front of the colonizing power (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
product of different experiences and learnings from training that has made it possible to articulate an analysis from which the body is one with social, cultural and historical Structo thus the family, as the primary institution in our life plays an important role in the definition of the identity. By meanings are constructed from reciprocal fashion, and in this case the body memory of emotions, so the ethnographic method facilitates exposure of the content address based on my own experience as a facilitator of processes of leads zgo and spirituality, which has allowed me to deepening theoretical and practical way in my personal experience and deepen the many ancestral knowledge that many times for not having only written records remain in the oral memory, but that also do not recognize themselves as valuable and professional.
Keywords: Health; Spirituality; Disease; Oral Memory; Ancestral Knowledge; Traditional Medicine